2022
DOI: 10.3389/fpubh.2022.997626
|View full text |Cite
|
Sign up to set email alerts
|

Effects of COVID-19-related psychological distress and anxiety on quality of sleep and life in healthcare workers in Iran and three European countries

Abstract: Introduction:The COVID-19 pandemic has considerably affected human beings most of whom are healthcare workers (HCWs) combating the disease in the front line.MethodsThis cross-sectional study aims to explore the effects of stress and anxiety caused by COVID-19 on the quality of sleep and life in HCWs, including physicians, nurses, and other healthcare staff. In this global study, we asked 1,210 HCWs (620 and 590 volunteers from Iran and European countries, including Germany, the Netherlands, and Italy, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
0
3
0
Order By: Relevance
“…Previous studies showed that regardless of their place of work, healthcare workers, mainly female nurses, experienced symptoms of anxiety and stress, which resulted in decreased sleep and quality of life [ 18 ]. Consistent with a previous study, we found that the front-line nurses were associated with severe sleep difficulty as they have a high risk of infection due to their heavy workload and long working hours [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that regardless of their place of work, healthcare workers, mainly female nurses, experienced symptoms of anxiety and stress, which resulted in decreased sleep and quality of life [ 18 ]. Consistent with a previous study, we found that the front-line nurses were associated with severe sleep difficulty as they have a high risk of infection due to their heavy workload and long working hours [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses from developing countries such as Iran and Ethiopia reported a poorer sleep quality in comparison to those from European countries. 80,81 One possible explanation for the higher occurrence of insomnia among healthcare professionals, especially those in regions with scarcer medical resources, is the increased fear of COVID-19 infection resulting from direct contact with the atypical coronavirus. Studies conducted on US physicians and Chinese nurses during the COVID-19 outbreak similarly showed an association between direct exposure to infected patients and insomnia.…”
Section: Infection Anxiety Post-traumatic Stress and Sleepmentioning
confidence: 99%
“…Specifically, nurses from Iran reported higher levels of psychological distress, greater fear of viral contraction, and consequently poorer sleep quality due to the lack of access to proper vaccines. 80 Another study conducted during the pandemic with Turkish healthcare workers revealed that general coronavirus anxiety, fear of COVID-19 infection, and perceived burnout collectively predicted the severity of insomnia symptoms. 78 In summary, these findings on infection anxiety across nations suggest that direct exposure to COVID-19 tends to significantly contribute to an elevated fear of COVID-19 infection, which in turn leads to an increased prevalence of insomnia among healthcare professionals during the pandemic.…”
Section: Infection Anxiety Post-traumatic Stress and Sleepmentioning
confidence: 99%
“…In a study of 1210 HCPs from Iran, Germany, Italy, and the Netherlands, no matter the setting, HCPs, and mainly female nurses, experienced stress and anxiety. This led to poorer sleep and decreased QOL [21]. In a cross-sectional study involving 218 HCPs, Abdelghani et al [22] discovered that all QOL dimensions were negatively connected with health anxiety due to the COVID-19 virus.…”
Section: Introductionmentioning
confidence: 99%